A organizaç\~ao coletiva de catadores de material reciclável no Brasil: Dilemas e potencialidades sob a ótica da economia solidária - Sandro Pereira Silva (Instituto de Pesquisa Econômica Aplicada (IPEA), 2017)
– The aim of this study was to analyze the structural characteristics of collective enterprises of pickers of recyclable material in Brazil, addressing questions about its administrative organization and its economic efficiency. Therefore, in addition to a wide bibliography that deals with the topic, it was also consulted the data from two nationwide surveys that provide important analytical overview on the structural dimensions of these enterprises. In general, the social segment of collectors involves people who are in situations of job insecurity, although practicing an admittedly beneficial activity for society. All information identified demonstrate that the developments are marked by a large structural heterogeneity, in a set of factors that directly impacts on the level of efficiency and labor productivity, the average income, working conditions and hence the satisfaction of collectors in be part of a collective enterprise.
Keywords: J54; Z13; 330; solidarity economy; pickers of recyclable material; collective organization; income generation; social inclusion policies